Dupilumab Efficacy and Safety as an Add-On Therapy in Uncontrolled Asthma Patients: A Systematic Review - Evelyn Evelyn; Putra Brillian Djohan; Fauna Herawati (Universitas Nahdlatul Ulama Surabaya, 2022)
Asthma is a heterogeneous chronic inflammatory condition affecting the lung. Standard treatment, a high-dose inhaled corticosteroid (ICS) and long-acting bronchodilator (LABA), effectively manages asthma in most individuals. However, 5%-10% of individuals with asthma were ineffective with those treatments. Recent RCTs suggested that Dupilumab posed potential as an add-on therapy. This systematic review aims to support the efficacy (the annualized rate of severe asthma exacerbation and increase in FEV1) and the safety of Dupilumab as an add-on therapy in uncontrolled asthma patients. We used "(Asthma) AND (Dupilumab)" as keywords on PubMed and ScienceDirect. We included only RCT design studies comparing the efficacy and safety of Dupilumab with a placebo in uncontrolled asthma patients. The placebo was ICS and LABA or oral glucocorticoids. This paper included five RCTs with 3400 participants, and their quality was assessed using Critical Appraisal Tools Program (CASP) tools. We conducted a meta-analysis to calculate the pooled risk ratio (RR). In addition, we used Mantel-Haenszel with 95% confidence intervals for dichotomous data. Furthermore, we used a random-effects model to count for interstudy heterogeneity. Then, we processed data using Revman 5.4. Dupilumab as an add-on therapy significantly showed a consistent effect in lower the annualized rate of severe asthma exacerbation (RR= 0.46; 95% CI 0.36- 0.58; p=0.007) and increased FEV1 compared to placebo. In addition, the most common adverse effect of using Dupilumab were injection site reaction, upper respiratory tract infections, and eosinophilia. In conclusion, Dupilumab is safe and well-tolerated as moderate-to-severe uncontrolled asthma add-on therapy